The use of satellite TV channels for social networks by promoting interactive participation with the Iraqi public regarding political issues - Al-Zuhairi, Arshad Yassin; Al-Samer, Abdel Salam Ahmed (Al-Adab Journal, 2021)
The essence of our research is to ask the question: How did satellite television channels employ social networks to enhance interactive participation and create an interactive environment with the Iraqi public regarding Iraqi, regional and international political issues? With knowledge about Iraqi political issues, the extent to which interactive tools are available, what satellite channels can enhance participation, the geographical scope of issues, the volume of publications, and interactivity. This research aims to investigate the volume of Interactive "Comments, Views, Likes, Posts" and knowing the number of posts on the "Al Sharqiya" channel on the networks "Facebook, Twitter, YouTube" regarding Iraqi political issues, the formats of the posts, the nature of trends, and the use of the survey method, and the method of content analysis, to examine the content of specific information to depict the actual reality of hiring boundaries.